acoustic metamaterials – new materials for acoustic electronics - Samoylovich, Mikhail; Belyanin, Alexey; Tcherniega, Nikolay (Видавництво Львівської політехніки, 2010)
Experimental results of the investigations of the photon-phonon interaction in orderly packed silica dioxide (opal matrices) and nanocomposites on their base are presented.
Keywords: photon-phonon interaction; opal matrices; acoustic vibrations of nanospheres